(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The essence of this scientific article is that Chronic caries: characteristic signs, treatment methods. General information about secondary dental caries, types of depressurization and its recurrence, etiology and many other information are provided.